The Role of Cultural Indoctrination in Architectural Style: Religion as a Mediator - Koc, Gulsah; Christiansen, Bryan (IGI GLOBAL, 2017)
This chapter examines the potential influence of cultural indoctrination (CI) on architectural style worldwide. Based on an encompassing literature review, this chapter focuses on the mediator of religion among the seven factors which are included in the established conceptual framework for CI; namely, Child Development, Cultural Institutionalization, Cultural Intelligence, Social Learning Theory, Religion, Social Capital, and Values Orientation Theory (VOT). The conceptual framework is presented for potential future application in architectural style and practice.
Keywords: SOCIETAL VALUES; Architecture; Cultural Studies